Los líquenes como indicadores de la contaminación atmosférica en el área metropolitana de San José, Costa Rica - Méndez A., Olga Isabel (1980)
Lichens were used as air pollution indicators in the metropolitan area of San Jose, Costa Rica. Trasplants showed a positive correlation between the percentage of dead cells in the thallus and the ketone soluble substances deposited on it. Those parts of the city where pollution is greatest (industrial areas and heavy traffic) were also the ones where lichens suffered the most, and in some extreme cases the thallus died after 8 months of exposure. Besides this transplant experiment, the coverage of Parmelia lichens on the bark of several tree species was determined in some areas of the city. The results of these observations suggest that the city of San José has three different kinds of air environment in relation to lichen survival: normal, transitional and desertic, as reported for other cities of the world. The most frequent air pollutants in San José are: CO, C02 , C2H5OH, Cl2, HCI, H2S, H3PO4, H2CrO4, NO, NH3, NH4 Cl, SO2 and Zn.